Vírus do ectima contagioso (ORFV): avaliação de vacina produzida em cultivo celular, investigação de persistência viral e filogenia de amostras brasileiras - Schmidt, Candice (2012)
Contagious ecthyma, also known as orf, is an infectious disease of sheep and goats caused by orf virus (ORFV), the prototype of the genus Parapoxvirus (PPV) of the family Poxviridae. Current vaccines against the disease contain virulent virus, are empirically produced through skin scarification of live lambs and present questionable efficacy. Likewise, the epidemiology of the infection, especially the mechanisms used by the virus to be perpetuated in herds and possible genetic and antigenic variations are poorly understood. Thus, the objectives of this study were: a. Development and efficacy testing of a vaccine produced in tissue culture; b. Investigation of viral persistence in experimentally infected lambs and, c. Phylogenetic analysis of Brazilian strains. Chapter 1 describes the development and testing of a ORFV vaccine produced in tissue culture. For this, ORFV strain IA-82 was submitted to 21 passages in BHK-21 cells and used to immunize lambs (n=30) through skin scarification of the internal face of the hind limb. Vaccination produced localized pustules and scabs lesions in 16 out of 30 animals, indicating an adequate replication of the vaccine virus. Ninety days after vaccination, vaccinated (n=16) and control lambs (n=16) were inoculated with a virulent ORFV strain in the labial commissure. Vaccinated and control lambs developed typical orf lesions, characterized by hyperemia, vesicles, pustules and scab formation. Nonetheless, vaccinated animals developed milder lesions compared to controls and the clinical scores were significantly lower (p<0.05) between days 10 and 22 post-challenge. In addition, the mean duration of clinical disease was significantly reduced in vaccinated animals (p<0.05). Furthermore, vaccinated animals excreted much less virus (p<0.05) and for a significantly shorter period of time than did the controls (13.4 days versus 22.6 days, p<0.001). These results demonstrate partial protection by the experimental vaccine and, upon improvement of immunization and protection indices, are promising towards the use of tissue culture-based ORFV vaccines. Chapter 2 presents the investigation of ORFV persistence in experimentally infected lambs. For this, infected lambs were monitored for virus and viral DNA at different intervals after infection. Concomitantly, virus viability in scabs maintained at environmental temperatures was monitored. During acute infection, virus produced typical lesions of ecthyma in all inoculated lambs (n=10), with lesions during over 22 days. Infectious virus was recovered from lesions in titers up to 105.5 TCID50/ml, with peaks of virus excretion between days 10 and 12 post inoculation (pi). The virus was detected continuously in lesions of all animals up to day 24 pi; four lambs shed virus until day 44 pi and one up to day 51 pi. Viral DNA was detected by PCR in all skin biopsies up to day 37 pi, in four animals at day 51, in three animals at day 65 and one at day 79 pi. Infectious virus was detected in scabs maintained under environmental temperatures for up to 6 months. These results demonstrate that ORFV may be maintained and excreted for a long period by infected animals. Chapter 3 presents the sequence analysis of the major envelope glycoprotein gene (B2L) of nine Brazilian ORFV strains from sheep and goats obtained between 2008 and 2011 and three vaccine strains. Comparative sequence analysis revealed that Brazilian strains were highly related among themselves and with vaccine strains. Brazilian strains shared 97.7- 100% and 96.1-100% sequence identity of nucleotides and amino acids, respectively. With vaccine strains, Brazilian ORFVs showed 98.7-100% nucleotide identity and 97.7-100% amino acid similarity. Phylogenetic analysis based on deduced amino acid sequences showed that the Brazilian strains from sheep and vaccine strains clustered in the same branches; goat strains clustered into a separate branch. In summary, the obtained results contribute to the knowledge about the ORFV biology and epidemiology and are promising towards the use of a tissue culture based vaccine.